The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1111/j.1460-9568.1997.tb01457.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoencephalography May Help to Improve Functional MRI Brain Mapping

Abstract: The validity of functional magnetic resonance imaging (FMRI) brain maps with respect to the sites of neuronal activation is still unknown. One source of localization error may be pixels with large signal amplitudes, since such pixels may be expected to overlie large vessels, running remote from the centre of neuronal activation. In this study, magnetoencephalography was used to determine the centre of neuronal activation in a simple finger tapping task. The localization accuracy of conventional FMRI depending … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Apart from these theoretical considerations, mismatches between electrophysiological and hemodynamic signals, in terms of quantity (Ureshi et al, 2005) and spatial distribution, have been detected in several experiments (Malonek and Grinvald, 1996;Beisteiner et al, 1997;Disbrow et al, 2000). The fMRI BOLD signal may reflect effects in cortical microvasculature or in large vessels (Frahm et al, 1994), the latter reducing spatial precision in regard to the underlying neuronal activity.…”
Section: Solving the Inverse Problem?mentioning
confidence: 95%
“…Apart from these theoretical considerations, mismatches between electrophysiological and hemodynamic signals, in terms of quantity (Ureshi et al, 2005) and spatial distribution, have been detected in several experiments (Malonek and Grinvald, 1996;Beisteiner et al, 1997;Disbrow et al, 2000). The fMRI BOLD signal may reflect effects in cortical microvasculature or in large vessels (Frahm et al, 1994), the latter reducing spatial precision in regard to the underlying neuronal activity.…”
Section: Solving the Inverse Problem?mentioning
confidence: 95%
“…Functional MRI can be criticized for being sensitive not only to parenchymal changes of blood flow but also to changes in large veins near the site of activation [Lai et al, 1993;Boxerman et al, 1995;Menon et al, 1995]. Beisteiner et al [1997] suggested that parenchymal activation could be discerned from signals arising in larger vessels, if signals with the highest amplitudes were excluded. Nevertheless, studies using magnetic resonance angiography have indicated fMRI activation of the typical SI areas, even in the absence of large veins over the central sulcus [Puce et al, 1995;Sakai et al, 1995].…”
Section: Comparison Of Fmri and Meg Localizations: Technical Aspectsmentioning
confidence: 99%
“…Some authors applied a multimodal noninvasive approach using MEG, fMRI, and motor evoked potentials and demonstrated that the combination of these techniques could further enhance the reliability for correct identification of central sulcus [129,130,131,132,133,134,135]. Finally, the results of MEG and fMRI localizations were integrated in frameless neuronavigational systems, providing the neurosurgeon with functional information in the eyepieces of the microscope.…”
Section: Localization Of Sensorimotor Cortexmentioning
confidence: 97%